EFL Pre-Service Teachers’ Problems during Teaching Assistance of Merdeka Belajar Kampus Merdeka Program - Rosanja, Nanda Eka Lana; Arapah, Elvina; Elyani, Eka Puteri (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
Teaching English was not an easy task. Therefore, pre-service teachers needed sufficient experience before becoming true teachers. The teaching assistance program was designed for aspiring teachers to gain that experience. However, during the implementation of this program, pre-service teachers undoubtedly encountered several problems. This study aimed to analyze the problems faced by pre-service teachers during the teaching assistance program. Three participants from the same university but different schools participated in the study. Questionnaires and interviews were used to collect data. The result showed that various problems were faced by pre-service teachers during teaching assistance. Almost all pre-service teachers encountered different problems compared to their peers during teaching assistance. However, some of them also shared similar problems. All the problems faced by pre-service teachers during teaching assistance could be categorized into two main factors. Internal factors such as inappropriate teaching method, material, media, classroom management and pre-service teachers’ proficiency. Then external factors such as problem related to students, disconnection between expectation and reality, school facility, and lack of relatedness between teaching practice alongside lectures. This was considered important to discuss so that in the future, pre-service teachers could be better prepared when they would teach directly to students at schools during teaching assistance.